1992
DOI: 10.1017/s0043174500058252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage, Crop Rotation, and Weed Management on Giant Foxtail (Setaria faberi) Population Dynamics and Corn Yield

Abstract: A long-term integrated pest management study initiated in 1980 and continued through 1991 was conducted to determine interactions of tillage, crop rotation, and herbicide use levels on weed seed populations, weed populations, and crop yield. This paper presents giant foxtail seed population and stand along with corn yield in continuous corn, corn rotated with soybean, or corn following wheat in a soybean-wheat-corn rotation. Increasing herbicide use levels above the minimum reduced giant foxtail seed in the 0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 27 publications
4
84
0
5
Order By: Relevance
“…Other studies show medium-disturbance tillage enhances control of certain weeds compared to NT + Res (Schreiber, 1992;Blackshaw, 1994;Cardina et al, 2002;Legere et al, 2011). Interestingly, of the studies showing more weeds in NT + Res compared to CT + Res, ones that report both yield and weed densities show that despite having more weeds, yields in rotated NT + Res are either equal to or higher than those in the rotated CT + Res systems (Schreiber, 1992;Legere et al, 2011). This may be because weed density may not be representative of weed biomass, which is more important when considering crop competition and yield reductions.…”
Section: Tillage Practice Interactions With Crop Rotationmentioning
confidence: 95%
See 3 more Smart Citations
“…Other studies show medium-disturbance tillage enhances control of certain weeds compared to NT + Res (Schreiber, 1992;Blackshaw, 1994;Cardina et al, 2002;Legere et al, 2011). Interestingly, of the studies showing more weeds in NT + Res compared to CT + Res, ones that report both yield and weed densities show that despite having more weeds, yields in rotated NT + Res are either equal to or higher than those in the rotated CT + Res systems (Schreiber, 1992;Legere et al, 2011). This may be because weed density may not be representative of weed biomass, which is more important when considering crop competition and yield reductions.…”
Section: Tillage Practice Interactions With Crop Rotationmentioning
confidence: 95%
“…In a study done in the mid-western US, researchers compared the maize phase of a two-(maize-soybean) and three-year (maize-soybean-wheat) rotation (Schreiber, 1992). Although the weed seedbank size did not differ between the rotations, regardless of tillage the maize in the three-year rotation had had lower weed densities compared to the maize-soybean rotation, meaning less of the seedbank germinated.…”
Section: Germination Of Weed Seedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ridging the soil just before canopy closure stiinulated germination of weed seed. The resulting weed population roduced up to 1000 seeds/in2 in continuous Schreiber (1992) found that growing corn in a soybeadcorn or soybeadwheat (Piticurn aestivimz L.)/corn rotation greatly reduced giant foxtail seed in thc soil compared to corn grown continuously, regardless of herbicide use or tillage system. The effects of crop rotation and environmental conditions associated with years and locations were larger than tillage effects on weed species coinposition and abundance in two separate studies in Canada (Derksen et al, 1993;Thoinas and Frick, 1993 Ball (1992) reported that cropping sequence was the most dominant factor influencing species composition in weed seed banks.…”
Section: Crop Rotationmentioning
confidence: 99%